Synthesis, antibacterial activity, in silico ADMET prediction, docking, and molecular dynamics studies of substituted phenyl and furan ring containing thiazole Schiff base derivatives - Md. Din Islam; Joyanta Kumar Saha; Sumita Saznin Marufa; Tanmoy Kumar Kundu; Ismail Hossain; Hiroshi Nishino; Mohammad Sayed Alam; Md. Aminul Haque; Mohammad Mostafizur Rahman (PLoS ONE, 2025)
This study synthesized eighteen phenyl and furan rings containing thiazole Schiff base derivatives 2(a–r) in five series, and spectral analyses confirmed their structures. The in vitro antibacterial activities of the synthesized analogs against two gram-positive and two gram-negative bacteria were evaluated by disk diffusion technique. Compounds (2d) and (2n) produced prominently high zone of inhibition with 48.3 ±  0.6 mm and 45.3 ±  0.6 mm against B. subtilis, respectively, compared to standard ceftriaxone (20.0 ±  1.0 mm). However, the antibacterial potency of the compounds with furan ring was more notable than that of phenyl ring-containing derivatives. Molecular docking and dynamic study were performed based on the wet lab outcomes of (2d) and (2n), where both derivatives remained in the binding site of the receptors during the whole simulation time with RMSD and RMSF values below 2 nm. In silico ADMET prediction studies of the synthesized compounds validated their oral bioavailability. A more detailed study of the quantitative structure-activity relationship is required to predict structural modification on bioactivity and MD simulation to understand their therapeutic potential and pharmacokinetics.